2012
DOI: 10.1002/chem.201103366
|View full text |Cite
|
Sign up to set email alerts
|

Direct Regiospecific and Highly Enantioselective Intermolecular α‐Allylic Alkylation of Aldehydes by a Combination of Transition‐Metal and Chiral Amine Catalysts

Abstract: The first direct intermolecular regiospecific and highly enantioselective α-allylic alkylation of linear aldehydes by a combination of achiral bench-stable Pd(0) complexes and simple chiral amines as co-catalysts is disclosed. The co-catalytic asymmetric chemoselective and regiospecific α-allylic alkylation reaction is linked in tandem with in situ reduction to give the corresponding 2-alkyl alcohols with high enantiomeric ratios (up to 98:2 e.r.; e.r.=enantiomeric ratio). It is also an expeditious entry to va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(39 citation statements)
references
References 123 publications
1
35
0
3
Order By: Relevance
“…Subsequently, the addition of In 2012, Ibrahem, Córdova and coworkers reported chemo-and enantioselective direct α-allylic alkylation of aldehydes with allylic acetates using Pd(0)/secondary amines catalysts (Scheme 23). 26 In principle, the mechanism of the reaction is similar to that reported by List 29 Controlled study revealed that suitable counteranion on Pd had a special effect: when Pd(OAc) 2 was replaced with PdCl 2 , the product was not obtained. When the styrene whose hydroxyl group was protected with -Me group was used as substrate, no product formation was observed indicating ortho-phenolic hydroxyl group is essential for the reaction to …”
Section: Scheme 1 Rh/pd Catalyzed Enantioselective Allylic Alkylatiomentioning
confidence: 70%
“…Subsequently, the addition of In 2012, Ibrahem, Córdova and coworkers reported chemo-and enantioselective direct α-allylic alkylation of aldehydes with allylic acetates using Pd(0)/secondary amines catalysts (Scheme 23). 26 In principle, the mechanism of the reaction is similar to that reported by List 29 Controlled study revealed that suitable counteranion on Pd had a special effect: when Pd(OAc) 2 was replaced with PdCl 2 , the product was not obtained. When the styrene whose hydroxyl group was protected with -Me group was used as substrate, no product formation was observed indicating ortho-phenolic hydroxyl group is essential for the reaction to …”
Section: Scheme 1 Rh/pd Catalyzed Enantioselective Allylic Alkylatiomentioning
confidence: 70%
“…An activated h 3 p-allyl palladium electrophile was formed from allyl acetate.T his species was subject to nucleophilic attack to the least sterically hindered site from an enamine formed from the aldehyde and pyrrolidine.Later, the same group expanded the procedure to include as tereoselective version employing diarylprolinol silyl ether 1a, furnishing a-allylated products in 55-85 %yield and 84-96 % ee (Scheme 13). [77] Following these initial reports,t he strategy of combining the enamine activation of aldehydes with the transition-metal activation of suitable electrophiles has resulted in as eries of asymmetric a-functionalizations that would be difficult to achieve employing only one of the catalytic systems.A mong others,t hese include alkylation [78] and propargylation reactions. [79] As tereodivergent a-allylation was reported by the Carreira group (Scheme 14).…”
Section: Organocatalysismentioning
confidence: 99%
“…Thus, the design and discovery of novel cooperative catalytic systems to conquer this challenge are particularly pressing. In 2006, we discovered that C-C bond formation could be achieved by combining homogeneous transition-metal catalysis with aminocatalysis, and have since then developed dual catalytic systems for reactions, such as enantioselective α-allylic alkylaion of various carbonyl compounds1112, enantioselective β-alkylation of α,β-unsaturated aldehydes13, carbocyclizations of various enynes1415 and for the synthesis of homoallylboronates16. While successful, this methodology still suffers from drawbacks, the main being related to the use of homogeneous catalysts that are tedious to remove, resulting in inefficient separation, purification and recycling of the catalyst1718192021.…”
mentioning
confidence: 99%